2022
DOI: 10.1093/mrcr/rxac085
|View full text |Cite
|
Sign up to set email alerts
|

Possible case of polyarteritis nodosa with epididymitis following COVID-19 vaccination: A case report and review of the literature

Abstract: The global outbreak of coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus type 2 has prompted the rapid spread and development of vaccines to prevent the spread of the disease. COVID-19 vaccine has demonstrated excellent efficacy in reducing morbidity and severity of the disease, and most adverse reactions are very minor. However, some patients have been reported to develop autoimmune diseases, such as rheumatoid arthritis, myocarditis, Guillain-Barre syndrome, and vasculiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…A total of six patients belonged to medium vessel vasculitis (MVV) [36,49,54,104,111,141]. Among the MVV patients, one had cutaneous polyarteritis nodosa (PAN) [54], and the remaining five had systemic PAN.…”
Section: Medium-vessel Vasculitismentioning
confidence: 99%
See 2 more Smart Citations
“…A total of six patients belonged to medium vessel vasculitis (MVV) [36,49,54,104,111,141]. Among the MVV patients, one had cutaneous polyarteritis nodosa (PAN) [54], and the remaining five had systemic PAN.…”
Section: Medium-vessel Vasculitismentioning
confidence: 99%
“…Among the MVV patients, one had cutaneous polyarteritis nodosa (PAN) [54], and the remaining five had systemic PAN. Out of these, one patient presented with acute anterior uveitis, and magnetic resonance angiography (MRA) of the abdomen was suggestive of vasculitis involving the celiac trunk [49], and another patient had associated myalgia, and a muscle biopsy of the left gastrocnemius also showed fibrinoid necrosis [111]. Another patient had an acute kidney injury with a kidney biopsy that showed features of necrotising vasculitis and required cyclophosphamide and haemodialysis for 32 days [36].…”
Section: Medium-vessel Vasculitismentioning
confidence: 99%
See 1 more Smart Citation
“…Ohkubo et al reported a 61-year-old man diagnosed with PAN and epididymitis following the BNT162b2 vaccine. The patient was treated with prednisolone and antibiotics [ 10 ]. Prior analysis of the Vaccine Adverse Event Reporting System (VAERS) has described 10 cases of possible PAN from the HBV vaccine [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, vasculitis has been associated with COVID-19 infection, but to date no cases of PAN have been reported [36,37]. COVID-19 vaccines have been associated with PAN manifestations [38][39][40]. Like other vasculitides, PAN can be induced by the use of certain drugs, such as minocycline [41].…”
Section: Physiopathologymentioning
confidence: 99%